Chemical and Organoleptics of Red Rosella Tea Powder (Hibiscus Sabdariffa Linn) with Drying Time Variatios - Anggita Syahidah; Agustina Intan Niken Tari; Retno Widyastuti (Universitas Veteran Bangun Nusantara, 2022)
Herbal tea is a general term used for beverages that are not derived from the tea plant (Camelia sinensis). Processing of red rosella flowers into red rosella flower tea powder is an attempt to utilize the compounds present in red rosella flowers that are able to give character to the resulting tea product and make it easier to serve. Red Rosella flowers have a high antioxidant content, in addition, the benefits of red Rosella flowers include lowering blood sugar levels, lowering cholesterol, lowering uric acid, preventing hypertension, preventing stroke, preventing cancer, tumors and so on. This study aims to determine the effect of drying treatment using an oven on the chemical and organoleptic characteristics of red Rosella tea powder using the oven drying method. This study used a completely randomized design (CRD) with one factor, namely the length of drying time (1 hour, 2 hours, and 3 hours) and compared with the control with 3 replications, in order to obtain 12 experimental units. Observation parameters include chemical properties (moisture content, ash content, antioxidant activity) and organoleptic properties (color, taste and flavor). The color and taste parameters had a significant effect, while the flavor parameter had no significant effect. The best treatment for Rosella flower tea was in the 2-hour drying treatment with a moisture content of 7.38% and an ash content of 5.27% in accordance with SNI 3836:2013 of packaged dry tea, as well as the organoleptic test with the highest value in the color test. Keywords: Tea, Herbal Tea, Rosella, Drying.